2010
DOI: 10.1177/1063426609353762
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Group Size on Classroom On-Task Behavior and Work Productivity in Children With ADHD

Abstract: This study sought to systematically examine the academic behavior of children with ADHD in different instructional contexts in an analogue classroom setting. A total of 33 children with ADHD participated in a reading comprehension activity followed by a testing period and were randomly assigned within days to either small-group instruction, whole-group instruction, or independent seatwork. The effects of instructional contexts on on-task behavior during instruction and on-task behavior and work productivity du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 43 publications
1
46
1
1
Order By: Relevance
“…Students with ADHD can benefit from accommodations such as small group instruction (Hart et al 2011) and computer-based testing (Lee et al 2008). Also, given the considerable overlap between ADHD and learning disabilities and motor dysfunction, accommodations that are effective for these co-occurring conditions (e.g., reading tests aloud to children with reading disabilities; Tindal et al 1998) are likely to benefit many children with ADHD.…”
Section: Does Adhd Treatment Improve Outcomes?mentioning
confidence: 98%
“…Students with ADHD can benefit from accommodations such as small group instruction (Hart et al 2011) and computer-based testing (Lee et al 2008). Also, given the considerable overlap between ADHD and learning disabilities and motor dysfunction, accommodations that are effective for these co-occurring conditions (e.g., reading tests aloud to children with reading disabilities; Tindal et al 1998) are likely to benefit many children with ADHD.…”
Section: Does Adhd Treatment Improve Outcomes?mentioning
confidence: 98%
“…It should also be noted that little is known about which accommodations work in regular school settings for students with ADHD (i.e. not in special settings such as the laboratory) due to lack of data (Hart et al 2011). The interventional studies to date provide no firm basis for evidence-based practices for children with ADHD, whether in regular classes or in special classes, especially when long-term effects are in focus.…”
Section: Prior Researchmentioning
confidence: 99%
“…Among college students with ADHD, paced item presentation offered no performance benefits on computer-based testing (Lee, Osborne, Hayes, & Simoes, 2008). Hart and colleagues (2011) found that while small group instruction increased on-task behavior in the classroom among children with ADHD, small group testing actually reduced productivity for these children.…”
Section: Introductionmentioning
confidence: 94%